Feasibility of Ice Segregation Location by Acoustic Emission Detection: A Laboratory Test in Gneiss - S. Duca; C. Occhiena; M. Mattone; L. Sambuelli; C. Scavia (Permafrost and Periglacial Processes)
Large slope failures in steep alpine bedrock present significant geological hazards. Ice segregation is thought to be one of the mechanisms involved in high‐mountain bedrock fracture but has not been reproduced experimentally in hard, intact rock. Here, we report results from a 3 month freezing experiment that aimed to reproduce ice‐lens growth at the interface between the active layer and permafrost in a 15 cm cube of hard, intact rock (Arolla gneiss). Monitoring of acoustic emissions (AEs) recorded the propagation of microcracks horizontally through the block, resulting in a continuous and thick macrocrack near the base of the artificial active layer. Microcracking occurred within an approximate temperature range of −0.5 °C to −2.7 °C, consistent with ice segregation theory. Hypocentres of recorded AE events were concentrated in a 40 mm thick band between depths of 4.5 and 8 cm in the block. The band approximately coincides with the frozen fringe and indicates that ice segregation can induce micro‐ and macrocracking in gneiss. Copyright © 2014 John Wiley & Sons, Ltd.